Meningkatkan Kualitas Pelayanan Publik Melalui Inovasi MARI-SERBU di Kecamatan Sukodono, Sidoarjo - Syahrani, Regita Pinkan; Wahyudi, Kalvin Edo (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The MARI-SERBU (Malam Hari Senin Rabu) innovation in Sukodono District, Sidoarjo, is a public service that operates in the evening, specifically on Mondays and Wednesdays from 6:00 PM to 8:00 PM. This program, managed by the District Office, provides services for managing population administration. This innovation offers a solution for people who are busy during regular working hours, allowing them to take care of their population documents. This study aims to describe the implementation of the